Exploiting material softness to regulate mesenchymal stem cells secretome production for "cell-free" regenerative medicine - Yang, Haibo (Nanyang Technological University, 2020)
Mesenchymal stem cells (MSCs) are multipotent stem cells derived from various adult tissues. They have been widely used in regenerative medicine because of their capability to differentiate into a variety of cell types. However, the paradigm of MSCs therapy shifts from differentiation to the secreted trophic factors of MSCs. MSCs secretome is a collective term for growth factors, chemokines, and cytokines and a variety of biologically active molecules secreted by MSCs. The therapeutic value of MSCs secretome has been proven in the treatment of cardiovascular diseases, liver diseases, and brain diseases, etc. To activate MSCs and engineer MSCs secretome for regenerative medicine, various preconditioning methods, including gene modification, drug treatment, hypoxia culture, etc., are adopted. Considering the sensitivity of MSCs to their microenvironment, biomaterials of different properties could be a potent regulator of MSCs secretome.